Community Preference towards Sea Fish in Tangor Market, Mentangor Village, Kulim District, Pekanbaru, Riau Province - Meidy, Refianov Hawali; Bathara, Lamun; Warningsih, Trisla (Fakultas Perikanan dan Kelautan Universitas Riau, 2024)
This research was carried out in December 2023 at Tangor Market, Mentangor Village, Kulim District, Pekanbaru City, Riau Province, with the aim of 1) Analyzing people's preferences for marine fish, marine fish, and the relationship between people's preferences for sea fish at Tangor Market. The research method used was a quantitative survey, and the number of respondents in this research was 37 who bought sea fish. Meanwhile, to answer the research aim, the researcher used Likert Scale data analysis to answer the first and second aims, while to answer the third aim, the researcher used Spearman Rank data analysis. The results of the research show that people's preference for sea fish at Tangor Market has a total Likert Scale of 38, meaning that people's preference for sea fish at Tangor Market is quite good and sea fish at Tangor Market has a total Likert Scale of 57, meaning sea fish at Tangor Market is quite good. In this research, people's preference for sea fish is used as a variable with a value of 0.000, meaning the level of closeness of the relationship between the two variables is very low.